Nurturing Nationalism: A Qualitative Study of the Role of the Ansor Youth Movement and Muhammadiyah Youth in Defending the Nation as a Form of Civic Involvement - Adhari, Nursanda Rizki; Sundawa, Dadang; Darmawan, Cecep; Syaifullah, Syaifullah; Basit, Abdul (ASANKA : Journal of Social Science and Education, 2025)
This article explores the strategic contributions of two Islamic-based youth organizations. Ansor Youth Movement and Muhammadiyah Youth are working to actualize the values of national defense and strengthen civic engagement amid contemporary socio-political challenges in Indonesia. The background of this study is rooted in the urgent need to revitalize the concept of national defense, which is no longer limited to militaristic dimensions but also involves the role of citizens in maintaining social integration, interfaith tolerance, and national unity. This research employs a descriptive qualitative approach with a case study method, conducted in Tangerang Regency, Banten Province. Data were collected through in-depth interviews, participatory observations, and document analysis, then analyzed using data reduction, thematic categorization, and interpretive meaning analysis. The findings reveal that the actualization of national defense by both organizations is implemented through cadre education, leadership training, and public advocacy grounded in national and religious values. Their involvement in cross-identity social actions, collaboration with the government, and efforts to counter intolerance serve as tangible forms of active citizenship. Furthermore, the development of social capital through solidarity, norms of reciprocity, and trust networks has proven crucial in strengthening civic resilience and national security. This article recommends the enhancement of harmony between youth organizations, government institutions, and educational entities in constructing an inclusive, critical, and value-based model of citizenship.